Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.febslet.2004.09.027
|View full text |Cite
|
Sign up to set email alerts
|

An angiotensin II AT1 receptor antagonist, telmisartan augments glucose uptake and GLUT4 protein expression in 3T3‐L1 adipocytes

Abstract: Evidence has accumulated that some of the angiotensin II AT1 receptor antagonists have insulin-sensitizing property. We thus examined the effect of telmisartan on insulin action using 3T3-L1 adipocytes. With standard differentiation inducers, a higher dose of telmisartan effectively facilitated differentiation of 3T3-L1 preadipocytes. Treatment of both differentiating adipocytes and fully differentiated adipocytes with telmisartan caused a dose-dependent increase in mRNA levels for PPARgamma target genes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 47 publications
(55 reference statements)
5
57
1
2
Order By: Relevance
“…Recently, it was shown to be a partial agonist of the peroxisome proliferatoractivated receptor (PPAR)γ in cultured cells [3,4] and to activate PPARα in cultured hepatic cells and in liver of wild-type mice fed a high-fat diet (HFD) [5]. Telmisartan has also been reported to improve HFD-induced obesity, insulin resistance and fatty liver in wild-type animals [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown to be a partial agonist of the peroxisome proliferatoractivated receptor (PPAR)γ in cultured cells [3,4] and to activate PPARα in cultured hepatic cells and in liver of wild-type mice fed a high-fat diet (HFD) [5]. Telmisartan has also been reported to improve HFD-induced obesity, insulin resistance and fatty liver in wild-type animals [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This effect may be related to the insulin-sensitizing effect of telmisartan in our study. On the other hand, recent studies have shown that telmisartan ameliorated mitochondrial energy metabolism in skeletal muscle and enhanced glucose uptake in adipocytes accompanied by an increase in GLUT4 expression (12,13) F i g u r e 1 . Ch a n g e s i n h o me o s t a s i s mo d e l a s s e s s me n t o f i n s u l i n r e s i s t a n c e ( HOMA-R) a f t e r 4 we e k s o f t e l mi s a r t a n a n d v a l s a r t a n a d mi n i s t r a t i o n . …”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Indeed, a number of clinical and experimental studies have already been conducted, which provide evidence for the beneficial effects of telmisartan in cases of type 2 diabetes, as well as metabolic syndrome and obesity. [14][15][16][17][18][19][20] Although the molecular mechanism required for the selective PPARg modulator phenotype is still unknown, partial agonism is assumed to be a typical and essential characteristic of selective PPARg modulator. 9,13 Telmisartan exhibits this critical feature, 9 and here we describe a crystal structure of human PPARg in complex with telmisartan that clarifies the mechanism of partial agonism.…”
Section: Introductionmentioning
confidence: 99%